Systemic usury and the European Consumer Credit Directive - Doris Neuberger; Udo Reifner (Universität Rostock, Institut für Volkswirtschaftslehre, 2019)
Usury is a frequent occurrence in consumer credit markets and particularly affects low-income households. Although the term usury conjures images of a greedy individual consciously acting to exploit the weak bargaining position of another by deceitful and even fraudulent means, we consider it as a systemic issue: as a problem of social discrimination, where belonging to a group which is statistically discriminated against leads to entrapment in a chain of usurious credit and financial contracts. This paper reviews the economic rationale for usury legislation and evaluates the European Consumer Credit Directive 2008/48/EC in this context. It identifies systemic usury as the product of market failure: the most powerful explanations for which are monopoly power, where the consumer is locked in a bilateral credit relationship; discrimination through risk-based pricing, and negative externalities. Contrary to the main focus of the European Consumer Credit Directive, improved disclosure of contract terms and other relevant information to consumers at the point of contracting cannot address systemic usury in credit markets. Even fully informed consumers can be discriminated against and become trapped in a situation of bilateral monopoly. As a consequence, the Directive is found to be ineffective: it implicitly acknowledges usurious practices and products as legal and undermines the national fight against usury. The Directive must be reformed.
Keywords: D14; D18; D42; D62; D63; G21; G28; K15; K22; K33; L12; L14; 330; discrimination; Consumer Credit Directive; incomplete information; payment protection insurance; overindebtedness; monopoly power; responsible lending; risk-based pricing; usury